1999
DOI: 10.1007/bf02236199
|View full text |Cite
|
Sign up to set email alerts
|

Patient and surgeon ranking of the severity of symptoms associated with fecal incontinence

Abstract: Evaluation of the Fecal Incontinence Severity Index indicates that the index is a tool that can be used to assess severity of fecal incontinence. Overall, patient and surgeon ratings of severity are similar, with minor differences associated with the accidental loss of solid stool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
490
1
9

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 741 publications
(502 citation statements)
references
References 13 publications
2
490
1
9
Order By: Relevance
“…MRP gradually recovered over time after ISR,14, 15, 19 and anal function improved over time 23, 27. Some authors reported that colonic J‐pouch anastomosis offered superiority in bowel frequency, urgency control, tolerable volume, Wexner score, and fecal incontinence severity index (FISI)77 compared with the straight anastomosis 20, 43, 78. Moreover, the C‐pouch and smooth muscle plasty procedures improved anal function following ISR 30, 44.…”
Section: Discussionmentioning
confidence: 99%
“…MRP gradually recovered over time after ISR,14, 15, 19 and anal function improved over time 23, 27. Some authors reported that colonic J‐pouch anastomosis offered superiority in bowel frequency, urgency control, tolerable volume, Wexner score, and fecal incontinence severity index (FISI)77 compared with the straight anastomosis 20, 43, 78. Moreover, the C‐pouch and smooth muscle plasty procedures improved anal function following ISR 30, 44.…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, this is a relevant finding, because evaluation of FI with FISI alone would also include a valid evaluation of QOL, and thus QOL would not have to be tested separately. Using a similar approach, we also tried to see whether VAS for FI correlates with FIQOL subscales, but we found that the correlation was only significant with embarrassment and to a lesser extent with coping/behavior, similar to the findings in Rockwood's study [7], suggesting that those are the aspects of QOL that are of the greatest concern to patients with FI. Curiously, in both studies the depression/self-perception subscale was not significantly correlated with the severity of the symptom, whatever the reason might be, and this feature could be taken into account if further studies aimed at simplifying FIQOL evaluation are undertaken.…”
mentioning
confidence: 54%
“…Furthermore, the severity of FI and its impact on QOL, expressed in a VAS for FI and a VAS for QOL, only have a fair correlation, showing that they do not assess the same issues, which is also supported by the finding that VAS for FI only correlates significantly with FIQOL embarrassment. Rockwood et al [7] studied the correlation between FISI and FIQOL subscales and demonstrated significant correlations in lifestyle, coping/behavior, and embarrassment. In our opinion, this is a relevant finding, because evaluation of FI with FISI alone would also include a valid evaluation of QOL, and thus QOL would not have to be tested separately.…”
mentioning
confidence: 99%
“…Two other useful scales are the Fecal Incontinence Severity Index, a weighted scoring of symptom frequency, and the Fecal Incontinence Quality of Life Scale, which accounts for the impact on quality of life from fecal incontinence symptoms. 8,9 The Fecal Incontinence Quality of Life Scale uses 29 questions divided into the 4 scales of lifestyle, coping/behavior, depression/self-perception, and embarrassment. Any type of validated measure can be helpful to provide the physician a better sense of symptom severity and to track improvement after medical and surgical treatment.…”
Section: Discussionmentioning
confidence: 99%